A morphometric and genetic investigation of Opuntia engelmannii population variation in Africa. (3rd September 2022) - Mbonani, Siphosenkosi; Glennon, Kelsey L.; Byrne, Marcus J.
Abstract: Opuntia engelmannii Salm‐Dyck (Cactaceae:Opuntioideae) is a morphologically variable cactus that has invaded pasture lands in South Africa and Kenya. Biological control of invasive Opuntia species can be very successful when the correct agent is matched with the appropriate host. This research investigated the similarity (morphological and genetic) between several populations of O. engelmannii and a morphologically uniform, O. stricta, that occur in South Africa and Kenya to help understand the identity of the target weed. Spine and cladode morphology showed that the Limpopo (South African) and Kenyan populations were most similar, while the spiny Eastern Cape (South African) population was more similar to Opuntia stricta . Multivariate analysis showed that spine morphometry was a useful diagnostic character in identifying different putative O. engelmannii populations in the field. In addition, we used amplified fragments length polymorphisms to estimate genetic similarity and genetic structure among populations that represent the morphologically variable populations. There was relatively little differentiation in the population structure between the Limpopo and Kenyan populations. The spiny Eastern Cape population showed moderate genetic differentiation ( F ST  = 0.05 − 0.15) relative to other O. engelmannii populations and was genetically more similar to the O. stricta population. These results will facilitate the search for suitable biocontrol agents by directing future collections of the appropriate biotype of Dactylopius opuntiae Cockerell (Hemiptera: Dactylopiidae) to relevant populations of O. engelmannii in its home range. In addition, given the genetic similarity of the spiny Eastern Cape population to O. stricta, we recommend the efficacy of D. opuntiae ' stricta ' biotype be tested on the spiny Eastern Cape population as a potential biocontrol agent.